CAREER PLANNING AND DEVELOPMENT PROCESS OF ISLAMIC HUMAN RESOURCES: A CASE STUDY AT BANK BSI KCP MEDAN MUCHTAR BASRI - Aprilia, Shavira (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to describe the process of career planning and development of Islamic Human Resources at Bank BSI Syariah KCP Medan. The research method used is descriptive qualitative with a case study approach in Bank BSI Syariah KCP Medan. The results of the study indicate that the process of career planning and development of Islamic Human Resources consists of several stages, namely needs identification, program development, implementation, and evaluation. Factors influencing the process of career planning and development of islamic human resources include organizational culture, human resources, and management systems. The implication of this study is that the islamic banking industry should pay attention to the process of career planning and development of islamic human resources as one of the strategies to improve the quality of islamic human resources at Bank BSI KCP Medan Muchtar Basri.